Age‐Dependent Effect of Pediatric Cardiac Progenitor Cells After Juvenile Heart Failure. (5th May 2016) - Agarwal, Udit; Smith, Amanda W.; French, Kristin M.; Boopathy, Archana V.; George, Alex; Trac, David; Brown, Milton E.; Shen, Ming; Jiang, Rong; Fernandez, Janet D.; Kogon, Brian E.; Kanter, Kirk R.; et al.
Abstract : To investigate the role of age of human pediatric cardiac progenitor cells (hCPCs) on ventricular remodeling, the authors injected neonate, infant, or child hCPCs into rats with right ventricular heart failure. Mechanisms including migration and proliferation assays, as suggested by computational modeling, showed improved chemotactic and proliferative capacity of neonatal hCPCs compared with infant or child hCPCs. Thus, the reparative potential of hCPCs is age‐dependent. Abstract : Children with congenital heart diseases have increased morbidity and mortality, despite various surgical treatments, therefore warranting better treatment strategies. Here we investigate the role of age of human pediatric cardiac progenitor cells (hCPCs) on ventricular remodeling in a model of juvenile heart failure. hCPCs isolated from children undergoing reconstructive surgeries were divided into 3 groups based on age: neonate (1 day to 1 month), infant (1 month to 1 year), and child (1 to 5 years). Adolescent athymic rats were subjected to sham or pulmonary artery banding surgery to generate a model of right ventricular (RV) heart failure. Two weeks after surgery, hCPCs were injected in RV musculature noninvasively. Analysis of cardiac function 4 weeks post‐transplantation demonstrated significantly increased tricuspid annular plane systolic excursion and RV ejection fraction and significantly decreased wall thickness and fibrosis in rats transplanted with neonatal hCPCs compared with saline‐injected rats. Computational modeling and systems biology analysis were performed on arrays and gave insights into potential mechanisms at the microRNA and gene level. Mechanisms including migration and proliferation assays, as suggested by computational modeling, showed improved chemotactic and proliferative capacity of neonatal hCPCs compared with infant/child hCPCs. In vivo immunostaining further suggested increased recruitment of stem cell antigen 1‐positive cells in the right ventricle. This is the first study to assess the role of hCPC age in juvenile RV heart failure. Interestingly, the reparative potential of hCPCs is age‐dependent, with neonatal hCPCs exerting the maximum beneficial effect compared with infant and child hCPCs. Significance: Stem cell therapy for children with congenital heart defects is moving forward, with several completed and ongoing clinical trials. Although there are studies showing how children differ from adults, few focus on the differences among children. This study using human cardiac progenitor cells shows age‐related changes in the reparative ability of cells in a model of pediatric heart failure and uses computational and systems biology to elucidate potential mechanisms.